2020
DOI: 10.1038/s41467-020-15245-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature paddlewheel effect in glassy solid electrolytes

Abstract: Glasses are promising electrolytes for use in solid-state batteries. Nevertheless, due to their amorphous structure, the mechanisms that underlie their ionic conductivity remain poorly understood. Here, ab initio molecular dynamics is used to characterize migration processes in the prototype glass, 75Li 2 S-25P 2 S 5 . Lithium migration occurs via a mechanism that combines concerted motion of lithium ions with large, quasi-permanent reorientations of PS 4 3− anions. This latter effect, known as the 'paddlewhee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
243
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(266 citation statements)
references
References 98 publications
20
243
3
Order By: Relevance
“…Camacho-Forero et al [184], Kim et al [234], and Pan et al [235] performed additional computational studies on β-LPS. Smith and Siegel [236] showed that the "paddlewheel" mechanism combines the Li ion migration with quasi-permanent reorientations of PS 4 3anions in Li 2 S-P 2 S 5 glasses. In 2019, Zhou et al [222] investigated the ionic conductivity of Li 3+x [Si x P 1−x ]S 4 (0.15 < x < 0.33) prepared by solid solution methods using a mixture of Li 2 S, P 2 S 5 , Si, and S; 5 wt.% excess S was added to the mixture to fully oxidize Si.…”
Section: Lithium Phosphorus Sulfide Electrolytementioning
confidence: 99%
See 2 more Smart Citations
“…Camacho-Forero et al [184], Kim et al [234], and Pan et al [235] performed additional computational studies on β-LPS. Smith and Siegel [236] showed that the "paddlewheel" mechanism combines the Li ion migration with quasi-permanent reorientations of PS 4 3anions in Li 2 S-P 2 S 5 glasses. In 2019, Zhou et al [222] investigated the ionic conductivity of Li 3+x [Si x P 1−x ]S 4 (0.15 < x < 0.33) prepared by solid solution methods using a mixture of Li 2 S, P 2 S 5 , Si, and S; 5 wt.% excess S was added to the mixture to fully oxidize Si.…”
Section: Lithium Phosphorus Sulfide Electrolytementioning
confidence: 99%
“…The lithium phosphorus sulfide (Li 3 PS 4 , LPS) electrolyte was derived from the (100 − x )Li 2 S– x P 2 S 5 binary system for x = 25 [ 203 , 204 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 ]. The first report on LPS was published by Tachez et al [ 212 ] in 1984; later on, Eckert et al [ 213 ] performed solid NMR studies on these systems.…”
Section: Sulfide Solid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification method is generally coating, that is, by coating the surface of the LNMO material to form an indirect contact between the cathode and the LEs at the expense of increased impedance, it can reduce the impact of side reactions on the LNMO structure. The SEs are the key to the development of LIBs in the future, which can be mainly divided into Polymer solid electrolytes, [81] garnet solid electrolytes, [82] sulfide crystalline solid electrolytes [83] and glass solid electrolytes, [84] etc.. Liu et al [85] . adopted sulfobetaine zwitterions (ZI) and polyethylene oxide (PEO) to modify polysiloxanes, and the prepared SEs had a wide electrochemical window.…”
Section: Modification Methodsmentioning
confidence: 99%
“…A recent study on Na + -ion migration and PS 4 3− rotation in Na 11 Sn 2 PS 12 revealed their intimate coupling and further confirmed the “paddle-wheel” mechanism as a transient opening of a migration window along the Na + transport channels 41 . The “paddle-wheel” mechanism can be intrinsic not only in the crystalline solids with the rotational disorder of the polyanion groups, but also in amorphous solid electrolytes 42 .…”
Section: Ionic Transport and Defectsmentioning
confidence: 99%